The Effect of Transaction Costs on The Benefits of Hybrid Maize Farming in Dompu District, West Nusa Tenggara - Kurniawan, Dodo; Ananda, Candra Fajri; Adi S, Putu Mahardika; Khusaini, Moh. (Journal of International Conference Proceedings, 2021)
The characteristics of imperfect markets are characterized by the presence of transaction costs. One sector that is an imperfect market is the agricultural sector. The purpose of this study was to analyze the structure of transaction costs and the implications of transaction costs on the benefits of hybrid corn farming. The research method uses transaction cost analysis and multiple linear regression. The research was conducted in Dompu Regency, West Nusa Tenggara with 120 respondents as corn farmers. The results show that implementation costs are the component of transaction costs that have the highest percentage of 43.35%, then supervision costs are 28.37%, transportation costs are 20.61%, negotiation costs are 3.70%, information costs are 3.41% and coordination 0.57%. These transaction cost components are distributed in each hybrid corn farming cycle, among others; (1) birth cycle; (2) cropping cycle; (3) maintenance cycle; (4) supervision; (5) harvest cycle; and (6) postharvest cycle. The postharvest cycle is the cycle that has the highest percentage of 23.17%, then the maintenance cycle is 18.53%, the harvest cycle is 17.65%, the cropping cycle is 17.28% and the control cycle is 13.99%. Transaction costs have a positive and significant effect on the profits of hybrid corn farming.